Bundesdeutscher massenmedialer diskurs aus phonostilistischer sicht - Frumkina, А. L.; Фрумкіна, А. Л.; Фрумкіна, Арина Леонівна (Одеса, 2017)
Статтю присвячено проблемі вивчення варіативності звучного мовлення в сучасному федеративно-німецькому теледискурсі в умовах фоностилістичного варіювання на матеріалі підготовленого читання та підготовлене говоріння дикторів та модераторів суспільно-правового телебачення Німеччини (канали ARD, ZDF, DW-tv).

The article focuses on the problem of studying functional style variability in spoken language in the modern German television discourse under the phonostylistical variety on the basis of read-aloud and prepared speech, which are presented by the most popular German shows, talk-shows, television news releases of the German public service television (ARD, ZDF, Deutsche Welle).
Frumkina, А. L. Bundesdeutscher massenmedialer diskurs aus phonostilistischer sicht / А. L. Frumkina // Одеський лінгвістичний вісник. – 2017. – Вип. 10. – Т.1. – С. 121-124.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; функціональний стиль; варіативність; дискурс; підготовлене читання; підготовлене говоріння; диктор; модератор; глотальний приступ; приступи голосного; functional style; phonostilistical; variability; discourse; spoken language; mass media; moderator; glottal stop; vowel's stops